2017
DOI: 10.1371/journal.pone.0184238
|View full text |Cite
|
Sign up to set email alerts
|

The equilibrium between antagonistic signaling pathways determines the number of synapses in Drosophila

Abstract: The number of synapses is a major determinant of behavior and many neural diseases exhibit deviations in that number. However, how signaling pathways control this number is still poorly understood. Using the Drosophila larval neuromuscular junction, we show here a PI3K-dependent pathway for synaptogenesis which is functionally connected with other previously known elements including the Wit receptor, its ligand Gbb, and the MAPkinases cascade. Based on epistasis assays, we determined the functional hierarchy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 130 publications
(145 reference statements)
2
28
0
Order By: Relevance
“…There were just four significantly differentially 93 and has also been shown to play a role in inhibiting synapse formation, as one part of two antagonistic signaling pathways that act together to produce the correct number of synapses. 94 In the Q5 interval of interest ( Figure 6E), just two genes are significantly differentially expressed, Odorant-binding protein 28a (Obp28a) and ). An RNAi screen specific to neurons identified ergic53 as a candidate gene involved in the perception of very high temperatures.…”
Section: Identification Of Candidate Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…There were just four significantly differentially 93 and has also been shown to play a role in inhibiting synapse formation, as one part of two antagonistic signaling pathways that act together to produce the correct number of synapses. 94 In the Q5 interval of interest ( Figure 6E), just two genes are significantly differentially expressed, Odorant-binding protein 28a (Obp28a) and ). An RNAi screen specific to neurons identified ergic53 as a candidate gene involved in the perception of very high temperatures.…”
Section: Identification Of Candidate Genesmentioning
confidence: 99%
“…Mad is a transcription factor that regulates the expression of BMP response target genes 93 and has also been shown to play a role in inhibiting synapse formation, as one part of two antagonistic signaling pathways that act together to produce the correct number of synapses. 94 In the Q5 interval of interest ( Figure 6E), just two genes are significantly differentially expressed, Odorant-binding protein 28a (Obp28a) and…”
Section: Identification Of Candidate Genesmentioning
confidence: 99%
“…Being PI3K a shared element in several signaling pathways (Acebes and Morales, 2012), we explored two possibilities, 1) the insulin receptor canonical PI3K/Akt pathway, which is known to elicit pro-survival and cell growth responses (Basu et al, 2012;Dyer et al, 2016), and 2) the recently revealed pro-synaptogenesis pathway (Jordán-Álvarez et al, 2017). To assay the effect of the classical pathway effector, we overexpressed Target of Rapamycin (mTOR), a downstream factor of PI3K, and we analyzed the synaptic signal in abdominal motor neurons of 15 days-old adults.…”
Section: Protection From Synaptic Effects Takes Place Through Non-canmentioning
confidence: 99%
“…Class I phosphoinositide 3 kinase (PI3K) is involved in a signaling pathway that leads to synapse formation in Drosophila (Martín-Peña et al, 2006) and vertebrates (Cuesto et al, 2011). This synaptogenic pathway includes the type II BMP receptor Wit (wishfull thinking) and several MAPKs, but not mTOR or S6K, which are characteristic of other PI3K classical signaling pathways (Jordán-Álvarez et al, 2017). The noncanonical PI3K-mediated pathway for synaptogenesis is counterbalanced by a Mad/Medea regulated anti-synaptogenesis pathway (Jordán-Álvarez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation